Optimization of Novel Indazoles as Highly Potent and Selective Inhibitors of Phosphoinositide 3-Kinase delta for the Treatment of Respiratory Disease - Down, Kenneth; Amour, Augustin; Baldwin, Ian R.; Cooper, Anthony W. J.; Deakin, Angela M.; Felton, Leigh M.; Guntrip, Stephen B.; Hardy, Charlotte; Harrison, Zoe A.; Jones, Katherine L.; Jones, Paul; Keeling, Suzanne E.; et al. (Journal of medicinal chemistry, 2015)
Optimization of lead compound 1, through extensive use of structure-based design and a focus on PI3K delta potency, isoform selectivity, and inhaled PK properties, led to the discovery of clinical candidates 2 (GSK2269557) and 3 (G5K2292767) for the treatment of respiratory indications via inhalation. Compounds 2 and 3 are both highly selective for PI3K delta over the closely related isoforms and are active in a disease relevant brown Norway rat acute OVA model of Th2-driven lung inflammation.